Effect of different concentrations of green tea on Cryopreservation of German Shepherd dog - Abood , Nagham y; Aliawy, Asmaa Sh (International Journal of Indigenous Herbs and Drugs, 2023)
To investigate the Effect of adding different concentrations of green tea extract as an antioxidant on specific physical semen characteristics of German Shepherd dogs during various steps of frozen semen processing this study was carried out. A total (of 20) good Ejaculate semen samples were collected in a plastic bag from German Shepherd dogs aged 3-4 yearsIn different locations (dog breeding).To achieve the current study's main objectives, two experiments were designed through periods extended from the beginning of December 2021 until the end of May 2022. The investigations included studying the physical properties of raw Semen (ejaculate volume, semen color, consistency, motility percentage, progressive motility percentage, dead sperm percentage, sperm abnormalities percentage, and hypo-osmotic swelling test (HOST). After that, semen samples were diluted with Tris supplemented with antioxidants. The physical properties of Semen were followed after cooling and after freezing (post-thawing). In the experiment, ten ejaculates were collected. Dilution of Semen was performed with Tris supplemented with two T1, T2, and T3) were cooled slowly up to 5C and equilibrated, packed into 0.5 ml straws, and put in vapor nitrogen (-196C) for 5-10  minutes after that, stored for 48and 72 hr in liquid Nitrogen (-196C). Progressive motility percentage, dead sperm percentage, sperm abnormalities percentage, and hypo-osmotic swelling test (HOST) were evaluated after cooling and post-thawing (Submerging the straws in the water bath at 37C for 30 seconds). It can be concluded from the present study that adding green tea extract as an antioxidant to the semen extender improves the ability to freeze, especially in the treatment T3 (0.01 mg/5 ml) and the T2 (0.05 mg/5 ml). This additive can decrease the negative Effect of freezing in liquid Nitrogen compared to the control group.